An Exercise for Estimating Wild Ungulate Population in Gir by Road-strip Census - Ahmed, M. F. (Indian Forester, 1976)
An effort has been made to estimate wild ungulate population in Gir forest by road strip census. It was found that productivity of cheetal and sambhar, seems to be good. The sex ratio as well as doe and fawn ratio indicated an Increasing trend in population. Road strip count method was found to give reasonable, reliable result and cheaper too.